Chapter 3: Develop a Vision - Jones, Loretta (Ethn Dis, 2009)
The Vision stage is the development of the agreed-upon framework for the study, including identifying the issue, the community, the stakeholders, and major aspects of the approach. Achieving the Vision requires planning through a Framing Committee, agreeing on a vision by sharing perspectives and identifying commonalities or “win-wins” that hold the partnership together for community benefit, and evaluating the emergence of the Vision and the partnership. Here, we review tools and strategies.